Status and dynamic character of the orphan in the French novel sub-saharan Africa - (:unkn) unknown (My University, 2013)
The social and legal status of orphan accompanied during the last fifty years, mutations, often violent, sustained by the Central African societies. Due to the number of orphans, individual issues of social integration, also become a major concern. The novel writing poses with insistence, with the narrative and aesthetic resources of its own, the question of the place of orphans in the social order. All resources of a narrative imagination underlying (child witches, street children, child soldiers, etc.) Are convened to the debate. It will explore how the narrative figuration this character commits a type of writing related to the criticism of state institutions. This issue raises a number of questions on the relationship between narrative and sociopolitical organization models in Central Africa. African societies are counted and regulate the novel and the character of the orphan is a key player in L’Enfant aux larmes de sang , Allah n’est pas obligé, Les Larmes de Tsiana, Tarmac des hirondelles and Histoire d’un enfant trouvé.
Keywords: African Research